2006
DOI: 10.1109/tcad.2006.882119
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics for Area Minimization in LUT-Based FPGA Technology Mapping

Abstract: In this paper, an iterative technology mapping tool called IMap is presented. It supports depth-oriented (area is a secondary objective), area-oriented (depth is a secondary objective), and duplication-free mapping modes. The edge delay model, as opposed to the more common unit delay model, is used throughout. Two new heuristics are used to obtain area reductions over previously published methods. The first heuristic predicts the effects of various mapping decisions on the area of the final solution and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 26 publications
(22 reference statements)
0
61
0
Order By: Relevance
“…The benchmarks used are 20 large public benchmarks from the MCNC and ISCAS'89 suites found in previous work on FPGA mapping [22][11] [29] 7 . Table 1 shows four experimental runs.…”
Section: Resultsmentioning
confidence: 99%
“…The benchmarks used are 20 large public benchmarks from the MCNC and ISCAS'89 suites found in previous work on FPGA mapping [22][11] [29] 7 . Table 1 shows four experimental runs.…”
Section: Resultsmentioning
confidence: 99%
“…Illegal cuts were discarded during the cut generation phase. ABC also provides area-reducing post-mapping routines based on the area-flow concept [13], which we customized to target the new architectures.…”
Section: +4-lut [mentioning
confidence: 99%
“…It is worth reinforcing that recent work has shown that mapping quality is not compromised by using AIGs compared with other network representations [12]. The baseline mapper was executed in depth mode, which achieves the minimum depth mapping and then performs area-driven post-passes based on the area-flow concept [15]. We use 20 large combinational and sequential circuits commonly used in academic research.…”
Section: Experimental Studymentioning
confidence: 99%